Identifikasi Pola Pertumbuhan Melalui Pendugaan Hubungan Antara Ukuran-Ukuran Dimensi Tubuh Pada Sapi Putih Taro Betina Dewasa - Oka, Anak Agung; Dewantari, Made; Suranjaya, I Gede (Universitas Bengkulu, 2023)
This research evaluated the growth pattern of Taro white cattle by estimating the relationship between body dimensions by measuring 18 Taro white cattle periodically every two weeks for three months. Body dimensions measured were body weight (BW), body length (BL), chest circumference (CC), body height (BH), hip height (HH), and hip width (HW). The measured data were analyzed descriptively, and to estimate the relationship between body dimensions, Multiple Linear Regression analysis was used, followed by Step Wise. The results showed that the average body dimensions of Taro white cattle were: BW:183.61 ± 25.92 kg; BL: 113.36 ± 7.13 cm; CC: 143.93 ± 6.61 cm; BH: 109.79 ± 3.92 cm; HH: 108.68 ± 4.58 cm and HW: 32.96 ± 2.33 cm. Body weight (BW) as an indicator of the growth of Taro white cattle has genuine multiple linear relationships with BL, CC, BH, HH, and HW with the equation BW = 1.23BL + 2.29 CC - 0.24 BH + 0.11 HH + 1.97 HW – 336.63 with a coefficient of determination (R2) = 0.78. Then step-wise, a new regression equation is obtained: BW = 1.42 BL + 2.50 CC – 338.03 with a coefficient of determination (R2) = 0.80. The conclusion is the estimation of body weight as an indication of Taro white cattle growth can be best carried out by utilizing body length and chest circumference as estimating variables.